MicroRNA-325 targets lipocalin 15 to suppress proliferation, migration and invasion of breast cancer cells - Zhuangkai Liu; Hong Xu; Xiang Li; Ruishan Zhang; Jinghui Bai; Xinfeng Zhang (Archives of Medical Science, 2020)
Introduction Recent studies have proved the diverse roles of miRs in different cancer-related processes. This study was undertaken to determine the therapeutic implications of miR-325-3p in breast cancer.